2008
DOI: 10.1063/1.2937148
|View full text |Cite
|
Sign up to set email alerts
|

Structure and bonding of the MCN molecules, M=Cu,Ag,Au,Rg

Abstract: High-precision calculations are reported for the title series with M=Cu, Ag, Au, using CCSD(T) with the latest pseudopotentials and basis sets up to cc-pVQZ. The bond lengths for M=Cu, Ag, Au agree with experiment within better than 1 pm. The role of deep-core excitations is studied. The second-order spin-orbit effects are evaluated at the density functional theory level, including M=Rg. A qualitative bonding analysis suggests multiple M-C bonding. The calculated vibrational frequencies are expected to be more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 20 publications
9
40
0
Order By: Relevance
“…Our AuAC bond length falls inbetween the result obtained preivously for AuCN using MP2/cc-pVQZ (186.51 pm) and using CCSD(T)/cc-pVQZ/191.05 pm). [6] In both AuCN and RgCN, the metal-carbon bonds show multiple bond character, all considerably shorter than the sum of the single-bond atomic radii reported by Pyykk€ o. [34] For instance, in AuCN the sum of the single-bond atomic radii between Au and C is 199.00 pm, 9.82 pm longer than our calculated DKS/PBE/dyall-cvtz bond length.…”
Section: Group 11: Gold and Roentgeniummentioning
confidence: 56%
See 4 more Smart Citations
“…Our AuAC bond length falls inbetween the result obtained preivously for AuCN using MP2/cc-pVQZ (186.51 pm) and using CCSD(T)/cc-pVQZ/191.05 pm). [6] In both AuCN and RgCN, the metal-carbon bonds show multiple bond character, all considerably shorter than the sum of the single-bond atomic radii reported by Pyykk€ o. [34] For instance, in AuCN the sum of the single-bond atomic radii between Au and C is 199.00 pm, 9.82 pm longer than our calculated DKS/PBE/dyall-cvtz bond length.…”
Section: Group 11: Gold and Roentgeniummentioning
confidence: 56%
“…[12] In contrast, the lack of a natural abundance of the superheavy elements has limited the number of studies of compounds involving these superheavy elements. In particular, with the exception of RgCN, [6] there has been no studies of the cyanide complexes of Ds, Rg, and Cn reported previously in the literature. Patzschke and Pyykk€ o [13] studied the properties of darmstadtium carbonyl and carbide and compared them to platinum carbide and carbonyl and found that darmstadtium resembled platinum in its bonding properties.…”
mentioning
confidence: 99%
See 3 more Smart Citations